MICROPROPAGATION OF GARDENIA Gardenia jasminoidesBY USING SINGLE NODES - Mosleh M.S.Duhoky (Mesopotamia Journal of Agriculture)
The present study was carried out to study the micropropagation of Gardenia (Gardenia jasminoides) by using single nodes excised from soft cuttings using half strength MS salts, 30gl-1 sucrose, 7gl-1 Agar and different concentrations of plant growth regulators in culture medium. Results of the experiment at initiation stage revealed that the culture of single nodes of Gardenia on a medium containing 5mgl-1BA gave the highest number of shoots (2.2 shoots/explant). Concerning the interaction, a nutrient medium containing (2 mgl-1 BA+ 0.4 mgl-1 IAA) gave the highest values of average number of shoots and leaves and length of new shoots (1.6 shoots/explant, 2 leaves/explant, 1.6cm respectively). At vegetative multiplication stage, the results showed that the medium supplemented by 2 mgl-1 BA gave the highest values of average number of shoots and leaves and length of new shoots (2.20 shoots/explant, 3.20 leaves/explant, 1.80cm respectively), whereas the medium supplemented by 0.3 mgl-1 IAA gave the highest number of shoots and length of new shoots. In order to promote the shoots produced at vegetative multiplication stage to root, it was noticed that the treatment of 8mgl-1NAA gave the highest percentage of rooting (90%) and the medium supplemented by 12mgl-1 IAA gave (100%) rooting. Plantlets obtained were transferred to pots and acclimatized with 95 % success.